Leadership of Nursing Administrator based on MOPH Core Value in Rangae Hospital, Narathiwat Province - Dulyakupt, Bunga; Namphiphat, Sunee; Hayeese, Wanisa (Princess of Naradhiwas University Journal, 2021)
This descriptive research aimed to study the leadership of the nursing administrator based on MOPH core value in Rangae Hospital, Narathiwat Province. Purposive sampling was used. The sample was divided into two groups, including 10 nursing administrators of Rangae Hospital and 95 nurses of Rangae Hospital. The research instruments were the demographic questionnaire, the Leadership of nursing administrators in the MOPH core value questionnaire, which was developed by a researcher, then verified by 3 experts. Content validity Indices (CVI) was 0.85, and Cronbach’s coefficients’ reliability was 0.96. Data were analyzed using descriptive statistics and Mann-Whitney U test. The result of this study revealed that: 1) The mean score of the nursing administrator’ leadership based on MOPH core value were at high level in both groups of nursing administrators and nurses ( = 3.96, S.D. = 0.39, & = 4.15, S.D. = 0.41, respectively), 2) comparison of leadership means scores between the opinions of the nursing administrators and the resident nurse’s group was no statistically significant difference. When considering each side, it was found that the mean of the study group, regarding patient care, significantly difference (P<0.05). The research findings revealed that nurses should implement the guidelines of the MOPH core values in developing nurse leadership skills. Self-development is a key factor in professional development to earn social acceptance. Also, the continual development in administration will increase efficiency within the Thai healthcare system.